KEPEMIMPINAN INSTRUKSIONAL DALAM KOMITMEN ORGANISASI GURU (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The significant influence of instructional leadership on teachers' dedication within educational institutions is evident. However, there's a noticeable absence in research that comprehensively analyzes instructional leadership practices between 2019 and 2024, particularly in Malaysia, Indonesia, Pakistan, and Thailand. This research aims to fill this void by conducting an extensive literature review focusing on the impact of principal instructional leadership on teacher commitment. By meticulously selecting 14 articles from national and international journals, this study reveals a consistent positive relationship between instructional leadership and teacher commitment across various Asian nations. These findings greatly enhance our theoretical understanding of how principal instructional leadership shapes teacher commitment within organizations, offering valuable insights for future research in this field.